Catastrophe Mechanism of Stress-Fissure Coupling Field in Mining Close Distance Seams in Southwest China. (2nd August 2021) - Jie, Suo; Zhen-hua, Li; Cun-han, Huang; Zheng-zheng, Cao; You-lin, Xu; Zu-guo, Chen
Abstract : For the sake of studying the catastrophe mechanism of stress-fissure coupling field in mining close distance seams in southwest China, a test working face in Guizhou province in southwest China is adopted and researched by the methods of numerical calculation and similar experiment. When the working face advances to 180 m in 4# coal seam in a similar experiment, the overlying rock breaks to the central base plate of Yulongshan limestone, and the conductive fractures run through the Changxing limestone karst cave and Yulongshan limestone karst cave. When the 1402 working face advances to 350 m, the top of vertical karst caves in the middle of the model produces extrusion damage, forming a penetrating water inrush passage. When the 1402 working face advances to 480 m, the top slab of the working face comes under periodic weighting with the short step. Besides, the mining of 9# coal seam starts after 4# coal seam in mining close distance seams. When the working face in 9# coal seam advances to 340 m in numerical simulation, the maximum opening of the overburden fractures is 51.16 mm. The fractures in the roof are mainly caused by the periodic breaking and falling of the basic roof, connected with the floor fractures of 4# coal seam. When the working face in 9# coal seam advances to 500 m, the maximum opening of the overburden fracture is 93.09 mm. Specifically, as the working face advances, the opening of fracture in the roof after collapse of the basic roof periodically is mainly greater than 5 mm, and the compaction closure is mainly 1 mm-5 mm. The fractures in the gob floor are mainly 0.1 mm-1 mm, and the fracture opening of the collapsed rock mass in the gob is mainly 1 mm-5 mm and greater than 5 mm. The karst caves in the overburden reduce the periodic weighting step of working face and play a guiding role in the direction of fracture development and water inflow passage formation. The karst caves are connected to surface waterfall holes and trap pits, and atmospheric precipitation recharges the water in the caves. The research results can be treated as an important basis for the prevention and treatment for water inrush disaster in mining close distance seams in the karst area of southwest China.